Performance Analysis & Evaluation in Cloud Computing: Challenges and Advantages of Cloud Computing Performance Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Cloud computing is a type of parallel, virtual, distributed, configurable, and flexible systems, which refers to provision of applications such as hardware’s and software’s in virtual data centers via internet cloud computing services are configurable and customers pay fees based on the use of resources and services. The most important element of cloud structure is server which is the brain behind the whole processes in cloud. Cloud is the important model for access to distributed computing resources. Pay per use, scalability, use the Internet technology, self-service based on the demand, high performance, quick to implement, easy to maintain and update are key benefits of cloud computing. And the data recovery, lack of control over cloud services, service level agreements, legal problems, different architectures, audit, Reviews and evaluation of the performance cloud computing environment are the major disadvantages of cloud computing.